Retention of Public Service Rehabilitation Staff: An Emperical Study - Luyolo Mahlangabeza (Mediterranean Journal of Social Sciences, 2022)
Human Resources Management (HRM) processes, working conditions and leadership have attracted the attention of researchers and practitioners due their importance for organisations. The study investigated the influence that HRM processes, working conditions and leadership have on retention of public service rehabilitation staff in South Africa. A quantitative research approach was adopted by distributing 82 self-constructed questionnaires of which 51 were returned. The results of the study found that HRM processes were significant and positively (r = 0.67, p < 0.05) related to staff retention. These processes included recruitment, staff development and renumeration. Leadership and changes in the working conditions will not lead to a significant retention of rehabilitation staff. The study provides guidelines for organisations to consider retaining staff in the rehabilitation services of the healthcare sector by applying effective HRM processes. Received: 20 February 2022 / Accepted: 10 June 2022 / Published: 5 July 2022